Unlocking Success: Innovative Education Marketing Strategies for Elementary School Enrollment Growth - Hasanudin, Kasmad; Srinio, Fuad; Warti'ah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
Building upon the aforementioned principles, SD NU Kaplongan endeavors to consistently deliver top-tier educational services, encompassing excellent facilities, quality assurance, and holistic character development. To complement these efforts, effective marketing strategies and a proficient teaching staff are essential in executing prepared initiatives. This study adopts a qualitative methodology, chosen for its compatibility with existing research and its aptness in analyzing community issues and mitigation efforts. Findings reveal that SD NU Kaplongan's marketing strategy is spearheaded by a dedicated core team responsible for community outreach and program promotion. This includes engagement with the new student admissions committee, followed by a comprehensive four-step marketing approach. The school offers a range of academic and extracurricular programs, yielding notable achievements and preparing students for enrollment in esteemed institutions such as state junior high schools and Madrasah Tasanawiyah. Moreover, promotional activities are extensively conducted through various channels, particularly leveraging social media platforms and alumni networks. Additionally, the school actively engages in community-oriented initiatives, organizing events such as competitions and religious activities to foster social cohesion and outreach.